A STUDIES ON THE DIFFICULTIES OF USING REGULAR AND IRREGULAR VERBS: ANALYSIS AND SOLUTION - Yani Octafia; Auliyah Pitri; Dharmayanti Aji Safitri (LPPM Universitas PGRI Jombang, 2026)
This research aimed to analyze the difficulties faced by senior high school students in mastering regular and irregular verbs in English learning and to identify possible solutions to overcome these difficulties. This study employed a qualitative method. The participants of this research consisted of ten twelfth-grade senior high school students and one English teacher in the academic year 2024–2025. The data were collected through writing tests with the students and the teacher to obtain information related to students’ learning difficulties, learning errors, and the causes of those errors in using regular and irregular verbs. The results of the study showed that students’ mastery of irregular verbs was still relatively low. Most students experienced difficulty in distinguishing between base forms, past forms, and past participles. Generally, they had difficulty differentiating regular and irregular verbs, tended to overgeneralize by adding -ed to all verbs, and had limited ability to memorize and recall the V2 and V3 forms of irregular verbs. In addition, instructional factors such as limited reinforcement and a focus on written grammar exercises rather than meaningful language use contributed to students’ difficulties. Therefore, this research suggests that English teachers should apply more contextualized and communicative teaching strategies with consistent reinforcement to improve students’ mastery of regular and irregular verbs.